Effects of a psychological intervention on Quality of life in infertile couples - Nasrin Abedinia; Fatemeh Ramezanzadeh; Ahmad Ali Noorbala (Tehran University of Medical Sciences, 2009)
Objective: This study aimed to determine factors affecting depression in infertile couples and effect of psychological intervention on pregnancy rate of infertile couples. Materials and Methods: In this study, 638 infertile patients referring to a university infertility clinic were evaluated. Among them, 140 couples with different levels of depression in at least one of the spouses were found and the study was continued by dividing them randomly into two groups, entering a randomized clinical trial. Patients in the case group received 6-8 sessions of psychotherapy before infertility treatment and were given daily Fluoxetin 20- 60 mg at the same period, and the control group did not receive any intervention. Three questionnaires including Beck Depression Inventory (BDI), Stress Scale (Holmes-Rahe) and a sociodemographic questionnaire were applied for all patients. Pregnancy rate was compared between two groups. Results: Depression was initially found in 48% of women and 23.8% of men. The mean±SD Beck scores fell from 18.7±9.7 to 10.7±5.8 in the group psychologically treated before receiving infertility treatment (P<0.001). Pregnancy rate was 47.1% in case group and 7.1% in control group. Pregnancy rate showed a significant relation with duration and cause of infertility and the level of stress in both groups (P< 0.001). Pregnancy rate was shown to be higher in couples with a second level of education in men (P< 0.001). Conclusion: The psychological intervention was found useful in alleviating depression and promoting pregnancy rate, it is crucial to mandate psychology counseling in all fertility centers.